2018
DOI: 10.1016/j.nano.2018.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Selective targeting and degradation of doxorubicin-loaded folate-functionalized DNA nanocages

Abstract: Selective targeting is a crucial property of nanocarriers used for drug delivery in cancer therapy. We generated biotinylated octahedral DNA nanocages functionalized with folic acid through bio-orthogonal conjugation chemistry. Molecular modelling indicated that a distance of about 2.5 nm between folic acid and DNA nanocage avoids steric hindrance with the folate receptor. HeLa cells, a folate receptor positive tumour cell line, internalize folate-DNA nanocages with efficiency greater than 40 times compared to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 62 publications
(64 citation statements)
references
References 56 publications
1
49
0
Order By: Relevance
“…Tetrahedra have also been used for miRNA detection, exploiting the optical properties of a fluorophore and a quencher [15]. Here we expand the use of truncated DNA octahedra, extensively characterized by us [19,23,24] as miRNA sequestering machines. These structures, modifiable on each truncated square face through the insertion of sequences complementary to different miRNAs, represent a ductile framework to act as multiple miRNAs sequestering units and restore the basal level of overexpressed oncomiRs in cancer cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tetrahedra have also been used for miRNA detection, exploiting the optical properties of a fluorophore and a quencher [15]. Here we expand the use of truncated DNA octahedra, extensively characterized by us [19,23,24] as miRNA sequestering machines. These structures, modifiable on each truncated square face through the insertion of sequences complementary to different miRNAs, represent a ductile framework to act as multiple miRNAs sequestering units and restore the basal level of overexpressed oncomiRs in cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…DNA nanostructures have also been functionalized to selectively interact with intracellular miRNA, mainly to detect their concentration, using electrochemical current or fluorescence signals [15][16][17]. Here, taking advantage of our experience matured in the last years in the characterization of different types of fully covalently octahedral DNA nanocages [11,12,[18][19][20][21], including their receptor-mediated cell targeting and their efficacy in selective drug delivery [5,22,23], we propose a new nanostructure for a possible therapeutic use as an efficient captor of the oncogenic miR21. For this purpose, we have initially engineered in one face of a truncated DNA cage four DNA hairpins complementary to a specific oligonucleotide (Fuel), to form a nanocage (H4-NC) with selective oligonucleotide sequestering activity.…”
Section: Introductionmentioning
confidence: 99%
“…S. Biocca (University of Roma “Tor Vergata”, Italy) in “Selective targeting of folate-functionalized DNA nanocages” described DNA-based nanostructures for delivering classical chemotherapeutic agents [32, 33]. DNA possesses intrinsic properties of high stability, biocompatibility and versatility that makes it an extremely suitable polymer for generating nanoparticles.…”
Section: Folate Receptors For Targeting Tumors and Inflammatory Diseasesmentioning
confidence: 99%
“…These data indicate the specificity of the aptamer‐modified TDNs for targeting cancer cells. In 2018, Raniolo et al decorated octahedral DNA nanocages with folic acid and assessed their uptake by HeLa cervix cancer cells that overexpress α‐folate receptor (αFR) . The authors showed that folate‐modified nanocages enter HeLa cells 40 times more than αFR‐negative A431 epidermal cancer cells, pointing to their specificity to αFR‐expressing cells after 24 h of incubation.…”
Section: Governing Factors Of the Cellular Uptake Of Dna Nanostructuresmentioning
confidence: 99%